计算:(x-y)分之2+y分之x-x分之1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 12:11:46
计算:(x-y)分之2+y分之x-x分之1计算:(x-y)分之2+y分之x-x分之1计算:(x-y)分之2+y分之x-x分之1通分:[2xy+x(x-y)x-(x-y)y]/[xy(x-y)]=(2x
计算:(x-y)分之2+y分之x-x分之1
计算:(x-y)分之2+y分之x-x分之1
计算:(x-y)分之2+y分之x-x分之1
通分:
[2xy+x(x-y)x-(x-y)y]/[xy(x-y)]
=(2xy+x³-x²y-xy+y²)/[xy(x-y)]
=(xy+x³-x²y+y²)/[xy(x-y)]
2/(x-y)+x/y-1/x
=2xy/[xy(x-y)]+(x^2)(x-y)/[xy(x-y)]-y(x-y)/[xy(x-y)]
=[2xy+(x^2)(x-y)-y(x-y)]/[xy(x-y)]
=[2xy+x^3-(x^2)y-xy+y^2]/[xy(x-y)]
=[x^3-x(x-1)y+y^2]/[xy(x-y)]
计算:y-x分之x+y+x-y分之y-y-x分之2x-y
计算:(x-y)分之2+y分之x-x分之1
计算 x-2分之x方+1-2-x分之3-4x (x+y)x方-y方分之x方+y-x分之y方
计算:x-y分之x+y-x分之y
计算:2x-y分之2x+y-2x分之y的结果是( )
计算[3x分之2-(x+y分之2)乘以[3x分之x+(y-x^2-xy)]除以x分之x-y
怎么计算x-y分之x^2-x+y
计算x-y分之2x + y-x分之 x-2y - x+y分之y的结果是() 化简(y-x分之1)÷(x-y分之1)的结果是
计算:(2y分之x)² ×2x分之y - y²分之x ÷ x分之2y²
计算:(2y分之x)² ×2x分之y - y²分之x ÷ x分之2y²,
计算(3y)分之2x+(3y)分之5x(3y)分之2x+(3y)分之5x(x+y)分之2y-(y+x)分之y-x(x²+3x)分之x²+9x+(x²+6x+9)分之x²-9
分式计算:x+y分之x^2-x+y=?(x+y分之x^2)-x+y=?
计算:(2x-y分之2x)+(y-2x分之y)
计算:(xy分之x+y)方-x方y方分之x方-y方
(y分之x减x分之y)除以(y分之x-2)除以(1+x分之y)
1.计算①(x-1-x+1分之8)×x+3分之x+1;②x+3y分之x-y÷x²+6xy+9y²分之x²-y²-x+y分之2y;③(x-x+1分之2x)÷x²-1分之x²-2x+1④(x²-2x分之x+2-x²-4x+4分之x-1)÷x³-2x²分之x-4
计算(x-y+2分之1)(x+y-2分之1)
x^-2-y-2分之x^-1-y^-1计算